157 - ANALYSIS OF BODY BALANCE OF GIRLS PRACTITIONERS AND NON-PRACTITIONERS OF DANCE (Fiep Bulletin - online, 2011)
One of the most important components of human movement is the ability to control his balance, and this worked well in the dance. The objective of this study was to analyze and compare the body balance of girls practicing and non practicing dance in the city of Macapa. This research is characterized by being kind of descriptive, exploratory and comparative cross-sectional, where 180 girls took part equally divided into two groups: GA (practitioners of dance) and GB (non-practitioners of dance). The instrument of data collection was the Scale of Motor Development (ROSA NETO, 2002), using as material a stopwatch sexagesimal. Our results indicate that the GA has, on average, higher driving age to chronological age, obtaining in this way, the classification of balance as high-normal, while the GB has motor age below their chronological age, classified balance in normal low. It follows therefore, that dance can help in the acquisition of the balance, which has been subsidizing its inclusion in the curriculum of the annual physical education classes, since they monopolize sports activities.
Keywords: girls; dancing and body balance